Learning with the body: a pedagogical project with refugee children combining elements of cooperative learning and theatre techniques - Vlachou, Sofia (Education & Theatre, 2022)
In this article, I will present a pedagogical project of embodied-experiential learning that I developed during my collaboration with refugee teenagers at their accommodation centre in Filippiada, Preveza in the 2020–21 fall/winter semester. This project arose from the children’s own imperative need to express to a familiar person who would be interested in listening to them the pain they experienced from being exposed to racist underestimation and rejection in their various daily interactions with local community members. Through the collaboration that followed, their initial narratives evolved into small theatrical acts, parts of an original "performance text" of public protest, that made this aspect of their reality visible to their wider social environment in a penetrating way. Emphasising once again the importance of theatre education for the learning and psychosocial enhancement of all students, without exception, I set as an ultimate goal of this article the initiation of a discussion on the development of creative methodologies and innovative tools of embodied learning. Such methodologies and tools could make great use of arts subjects and/or a more creative application of physical education in the frame of cross-curricular teaching in order to promote the inclusion of refugee children in their respective school environment.